Acute stroke intervention after transcatheter aortic valve replacement. Issue 4 (2nd October 2018) - Hamandi, Mohanad; Farber, Adam J.; Tatum, James K.; Brinkman, William T.; Brown, David L.; Lawrence, Mark E.; Mack, Michael J.
Abstract: Stroke is a devastating complication in patients undergoing transcatheter aortic valve replacement (TAVR). We sought to determine whether early stroke intervention after TAVR would improve the neurological outcomes. Two patients experienced stroke immediately after TAVR, one treated with mechanical thrombectomy and localized lytic therapy and one treated with systemic lytic therapy. Our limited experience showed that early stroke intervention with either treatment option may reduce the risk of complications and improve neurological outcomes.